Бобик в гостях у Барбоса - Носов Николай Николаевич (Эксмо, 2006)
Экземпляры: (201310) / Инвентарный номер: 48834 / Цена: 50.00 / Сис.шифр: Д 48834 / Авт.знак: Н 84 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6